MULTIMODAL DISCOURSE ANALYSIS OF SIA’S MUSIC VIDEO “ELASTIC HEART” - Peradze, Nato (Online Journal of Humanities ETAGTSU, 2022)
Multimodal analysis and Multimodal Discourse Analysis, which explore texts according to multiple modes of communication, have been widely researched in modern linguistics and cinematography. The article will analyze Sia’s music video “Elastic Heart” based on Halliday’s three metafunctions and Machine’s(2010) work: Analysing Popular Music: Image, Sounds and Text. We have used quantitative and qualitative methods of analysis. The metafunctions were employed to analyze the verbal information (also based on Castillo Acosta’s (2018) framework) while the visual components were studied quantitatively using Machin’s approach to the visual data. The article also demonstrates the importance of metaphoric thinking and the influence of multimodal metaphors in decoding the overall meaning of an art piece. The study finds that Sia’s song “Elastic Heart” predominantly employs material and mental processes, and identifies key conceptual metaphors, namely MENTAL ILLNESS IS A BOUNDED SPACE/DEPRESSION IS A BOUNDED SPACE realized simultaneously in two different semiotic modes and highlights the significance of metaphoric interpretation of visual elements in the music video. Full Text (PDF)